Affiliate Marketing SMES to Young Entrepreneurs in Yogyakarta City (Home Business Camp) - Nina Fapari Arif; Shely Rizki Hardiana; Asri Sekar Mawar Firdausi; Budi Purnomo Saputro; Hafidh Rifky Adiyatna (Yayasan Putra Adi Dharma, 2024)
The Community Service Program (PKM) conducted information research on the challenges faced by members of HBC in managing and developing their businesses. Challenges in business management and HBC management include marketing systems and efforts to expand markets. The objective of this training is to provide affiliate marketing training to HBC members with training materials relevant to their needs and to help them overcome challenges in business management. The method used is initial interviews to determine the required training themes, followed by training sessions and discussions on the conducted training. The training results indicate that Affiliate Marketing can expand market reach, enable the determination of online marketing strategies, allow SME players to work flexibly from anywhere and anytime as long as they have internet access, and enable them to schedule work according to their needs